On commercial Н⁻ cyclotrons up to 30 MeV energy range for production of medicine isotopes - Papash, A.; Alenitsky, Y. (Вопросы атомной науки и техники, 2008)
A compact isochronous cyclotrons to accelerate negative hydrogen ions up to 30 MeV are widely used for production of medical isotopes and other applications. The physical and technical parameters of accelerators are compared. Measures to improve performance and to increase beam intensity are proposed. Компактні ізохронні циклотрони негативних іонів водню в діапазоні енергій до 30 МеВ широко використовуються для виробництва медичних ізотопів і інших застосувань. Проведено порівняння і аналіз різних моделей прискорювачів. Запропоновано способи підвищення ефективності роботи і збільшення інтенсивності пучків. Компактные изохронные циклотроны отрицательных ионов водорода в диапазоне энергий до 30 МэВ широко используются для производства медицинских изотопов и других применений. Проведено сравнение и анализ различных моделей ускорителей. Предложены способы повышения эффективности работы и увеличения интенсивности пучков.